The love song of Miss Queenie Hennessy [large type] : a novel - Joyce, Rachel (Wheeler Publishing, 2015)
"When Queenie Hennessy is told she has days to live she sends a letter on pink paper in which she bids goodbye to Harold Fry. It is a letter that inspires an unlikely walk, a cast of well-wishers and the examination of many lives unlived. But there is a second letter, a longer, quieter more complicated letter which she will never send. It is this letter, the one we did not know about in The Unlikely Pilgrimage of Harold Fry, which reveals the shocking and beautiful truth of Queenie's life"--